Mejoramiento de potreros naturales de kikuyo (Pennisetum clandestinum) mediante el sistema de subsolación y aplicación de abono químico y orgánico en la quinta experimental Punzara de la Universidad Nacional de Loja - Cuenca Asanza, Osmany Alexander (2015)
The research was conducted at the Fifth prick the Agricultural Experimental Area and Natural Resources of the National University of Loja, which is located in the area South West Hoya de Loja. To this end the following objectives: To determine the effect of subsoiling system with the application of chemical and organic fertilizers on the production of green forage in farm prick the National University of Loja, calculate the cost of production two fertilization systems and also evaluate the efficiency of biomass yield and carrying capacity of natural prairie Kikuyu. The experimental units (plots) on the ground, were distributed simple random: Treatment one (T1): kikuyo with subsoiling more compost; Treatment two (T2): kikuyo without subsoiling more compost; Treatment three (T3): kikuyo with subsoiling more chemical fertilizer and Treatment four (T4): kikuyo without subsoiling more chemical fertilizer. Once you have done the research it came to determine that: The plant height of Kikuyu was higher in the treatment T3 as it recorded a greater height reaching 66.43 centimeters long, while the T2 reached a height of 51.80 cm. Biomass production Kg / ha it was higher and is directly related to the height of the plants so that the T3 production of biomass of 1.14 kg / m2 had,. The nutritional value of forage protein was higher in the T1 with an average of 12.72% protein, followed by T4 with 12.26% in Q3 a value 12.16% and slightly lower than in Q2 with 12.02%. The carrying capacity turned out to be 4.36 in Q3 UBA in T1 and T4 with receptive capabilities UBA 3.44 and 3.43 respectively, while the T2 receptive UBA capacity of 2.92 was achieved. And finally categorically profitability was higher in T1 (Subsoil and organic fertilization) with a value of 276.88%